SEMANTIC CHANGE ANALYSIS ON THE DIALOGUES IN NARRATIVE TEXT IN SECOND YEARS ENGLISH TEXTBOOK OF SENIOR HIGH SCHOOL - Pebri Prandika Putra; Harianti (Prologue: Journal on Language and Literature, 2024)
Semantic change is a form of language change regarding the evolution of wodrd usage-usually to the point that the modern meaning is radically different from the original usage. The research questions of the research are 1) What are the types of Semantic Changes Analysis on the Dialogues in Narrative Text in Second Years English Textbook of Senior High School? 2) What is the dominant type of Semantic Changes Analysis on the Dialogues in Narrative Text in Second Years English Textbook of Senior High School. This research approach uses a qualitative descrptive content analysis. Then this research use the theory proposed by palmer (1981).The research findings both in the textbooks 11 narrative text. The researcher found 15 data in generalization, in specialization the researcher found 5 data, in pejoration the researcher found 6 data and the researcher does not include namely type amelioration.